Peranan Guru Pembimbing Dalam Penyeliaan Latihan Mengajar - Mohamed, Abdul Rashid; Ismail, Zurida (Penerbit Universiti Sains Malaysia, 2002)
The involvement of schools in teacher education programs have been going on for years because the schools are seen as the most appropriate place to educate teachers. The school community has the teaching experience, background knowledge of the school, and understands the school atmosphere.